Establishment of a gravity calibration baseline with the constrain of absolute gravity measurements after 17 August 1999 Izmit earthquake in Marmara region, Turkey - Dogan, U.; Ergintav, S.; Arslan, G.; Demir, D. O.; Karaboce, B.; Bilgic, E.; Sadikoglu, E.; Direnc, A. (SPRINGER, 2013)
We described the first results of an on-going study of absolute gravity changes after the 17 August 1999 Izmit earthquake in Marmara region. Repeated absolute gravity measurements were carried out six stations with an A10 absolute gravimeter from 2009 to 2011 in the region. A gravimetric calibration baseline (of the range of about 415 milliGal (mGal), 1 mGal=10(-5) ms(-2)) was established in the region for the purposes of the calibration of the relative gravimeters. The absolute gravity measurements, repeated twice a year (October, June), can resolve gravity changes with a precision better than 5 microGal (mu Gal)/yr interval. The absolute gravity stations indicate a statistically significant gravity decrease at one of the absolute gravity stations in the calibration baseline, but the other stations do not. Generally, the absolute gravity difference agrees well with the general trend of the relative gravity changes. In addition, the precise vertical gravity gradients with relative gravity measurements have been determined at the absolute gravity stations for the reduction of measured gravity to the benchmark. The gradients scatter around the nominal constant (3.086 mu Gal/cm) between 2.82-3.73 mu Gal/cm as a result of the local density anomalies. The difference from the nominal gradient causes the error around 7-14 mu Gal by applying the normal vertical gradient instead of the directly measured one.
Keywords: Absolute gravimetry; Relative gravimetry; Vertical gradient; Calibration line; Marmara region; DEFORMATION; GRAVIMETERS; GRADIENT; Geochemistry & Geophysics